Penegakan Hukum Pemanfaatan Sumber Daya Panas Bumi pada Studi Kasus Pembebasan Lahan - Nova Novian Tika (Savana, 2024)
This study examines the utilization of geothermal resources in land acquisition cases, focusing on Ambon District Court Decision Number 36/Pid.Sus-TPK/2022. This study aims to analyze geothermal utilization regulations based on Indonesian positive law and the application of Lawrence M. Friedman's legal system theory to dispute resolution. The research method used is normative juridical with a statutory approach. The results indicate that the main obstacles to geothermal utilization are land acquisition conflicts, overlapping regulations, and a lack of community participation. The dispute in the Tulehu Geothermal Power Plant case indicates weak compliance with village financial management and transparency. The application of legal system theory demonstrates that harmony between legal structure, legal substance, and legal culture is necessary to resolve disputes and support the sustainable development of geothermal energy.